2004
DOI: 10.1007/s00464-003-9030-z
|View full text |Cite
|
Sign up to set email alerts
|

Hand-assisted laparoscopic surgery (HALS): a report of 150 procedures

Abstract: HALS is fast, safe, and feasible for various indications, especially HLDN and (procto-)colectomies. Little advantage can be expected when HALS is applied in splenectomy and segmental bowel (sigmoid) resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
30
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 27 publications
7
30
0
Order By: Relevance
“…The perioperative clinical outcomes of our patients undergoing HALS compared favorably with those reported in other contemporary HALS series for benign and malignant colorectal diseases [1,10,11,14]. In 2006, Schadde et al [11] reported 104 patients who underwent HALS over a five-year period for a variety of colorectal indications.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…The perioperative clinical outcomes of our patients undergoing HALS compared favorably with those reported in other contemporary HALS series for benign and malignant colorectal diseases [1,10,11,14]. In 2006, Schadde et al [11] reported 104 patients who underwent HALS over a five-year period for a variety of colorectal indications.…”
Section: Discussionsupporting
confidence: 66%
“…Several studies have examined the applicability of this technique to specific advanced colorectal procedures [9,10] but few have analyzed the role of HALS in a clinical practice involving patients with a variety of benign and malignant colorectal diseases [10][11][12][13]. Although available randomized comparisons of HALS versus LA have suggested that HALS maintains the patient-related benefits of LA colectomy while shortening operative times and allowing surgeons to perform more complex cases [1,14] these studies suffered from small sample sizes.…”
mentioning
confidence: 98%
“…Over the last 10 years, HALS technique has been employed for a variety of procedures. By far the most common indication is nephrectomy (Kercher et al 2003, Maartense et al 2004, Gaston et al 2004, Brown et al 2004). Other indications include liver resection (Fong et al 2000, Shimizu et al 2003, Hayakawa et al 2004), pancreas surgery (Doi et al 2003), splenectomy (Takahashi et al 2004, Bermas et al 2004, esophagectomy (Romanelli et al 2001), gastric bypass surgery and gastrectomy (Romanelli et al 2001, Sundbom andGustavsson 2004), colorectal surgery (Loungnarath and Fleshman 2003, Nakajima et al 2004, Kang et al 2004), aortoiliac surgery (Wijtenburg et al 2003), and hysterectomy (Pelosi and Pelosi 1999).…”
Section: Hand-assisted Laparoscopic Surgery In Human Medicinementioning
confidence: 99%
“…Beginning with the fi rst laparoscopic appendectomy performed by K. Semm (1) in 1983, advanced laparoscopic surgery has become an increasingly common practice as a result of technological developments, surgical curiosity, and medical ambition (2)(3)(4). In the past 30 years, laparoscopic interventions have been used in various fi elds for treatment of many malignant and benign diseases (4).…”
Section: Introductionmentioning
confidence: 99%
“…In the past 30 years, laparoscopic interventions have been used in various fi elds for treatment of many malignant and benign diseases (4). Currently, laparoscopy is preferred as an alternative to open surgery due to its low complication rates, less postoperative pain, achievement of better cosmetic results, and quicker return of patients to their daily lives (4,5).…”
Section: Introductionmentioning
confidence: 99%